Screen Time and University Students’ Life: Exploring the Impact of Smartphone Usage on Sleep Quality, Well-Being, Social Behavior, and Academic Performance - Daisy Mui Hung Kee; Bradley Batok Jim; Fikri Amir bin Mohd Razman; Danish Muqri bin Risby (AIBPM Publisher, 2025)
This study investigates the impact of smartphone usage on sleep quality, mental and physical health, academic performance, and social behavior, while also examining how sleep quality affects these factors. This study surveyed 224 university students to test nine hypotheses, using a five-point Likert scale. Data responses were analyzed with SPSS. The findings indicate that excessive smartphone use significantly reduces sleep quality, which in turn negatively affects mental and physical health, academic performance, and social interactions. Poor sleep quality is linked to increased stress, fatigue, and health issues, contributing to lower academic achievement and negative social behaviors. Furthermore, high smartphone usage is associated with decreased face-to-face interactions and social well-being. These results highlight the need for students to practice self-discipline in smartphone usage, as it can have both positive and negative effects. Promoting healthier digital habits and improving sleep quality are essential for enhancing students’ well-being and academic success. Universities and policymakers should consider interventions, such as awareness programs and digital detox strategies, to mitigate the adverse effects of excessive smartphone use. Addressing these challenges can help students achieve a better balance between technology use, health, and academic performance.